Specific therapeutic options for transthyretin amyloidosis - Zoltán Pozsonyi (Cardiologia Hungarica)
The epidemiology of systemic amyloidosis has recently undergone a spectacular transformation. While light-chain amyloidosis remains a rare disease with a stable incidence, chronic inflammatory disease associated amyloidosis (AA) is diagnosed less frequently, the incidence of the mutational and wild-type forms of ransthyretin amyloidosis (ATTR) has increased dramatically in the developed world. This pectacular increase can be explained by increased diagnostic awareness due to the emergence of new multi-targeted drugs and the spread of simpler, more easily accessible diagnostic methods. In this communication, we summarize the new specific therapeutic options for transthyretin amyloidosis and the new treatment modalities that are expected in the near future.